Studies on Innovating Business Activities Using Triple Bottom Line Concept: The Case of Building Hygene Company Valtex - Rant, Melita Balas (Modern Perspectives in Economics, Business and Management Vol. 4, 2021)
Valtex, a Slovene company that provides hygiene products for commercial buildings, up to recently operated successfully in the eyes of the CEO and owner Niko Kumar, meeting the expected growth, profit and cash flow. Yet suddenly the company is faced with the threat of bankruptcy which put past success on shaky grounds. Niko Kumar, together with his business partner and sales consultant, is forced to think deeper about the real value of the “building hygiene” business, its attractiveness in terms of triple bottom line (profitability, planet and people); and study the value – if any – Valtex really creates for customers, society (planet and people). Most importantly with bankruptcy at the horizon, Niko is forced to explore novel areas where Valtex would really create substantial value for the customer and society. The case is suitable for post graduate students of management, short duration executive education programs, executive MBA programs, and entrepreneurship education. When discussing this case with a goal of helping Niko Kumar to innovate novel business activities for Valtex using sustainability perspective, an instructor is advised to use a set of strategic concepts: Porter’s [1] five-force analysis and company activity system, Brandenburger and Stuart’s [2] concept of value adding activities, Elkington’s [3] concept of triple bottom line as well as train students in using brain-storming and other creative thinking techniques.